Emerging nonoxide dielectrics for next‐generation electronics - Kim, Ga Hye; Shin, Seung Beom; Kim, Myung‐Gil (Bulletin of the Korean Chemical Society, 2023)
As electronic devices continue to develop, there is a growing demand for materials capable of supporting new physical properties, such as flexibility, stretchability, low‐temperature processability, applicability to large areas or ultra‐thin films, and operation at extremely low voltages. Metal oxide dielectrics, such as silicon dioxide, aluminum oxide, and hafnium oxide, offer excellent dielectric properties, but their ability to meet these new properties and the choice of substrate is limited. Therefore, a new dielectric material capable of providing stable dielectric properties with new functionalities is required. In this review, we briefly introduce the physical principles of dielectric materials and the recent trends of nonoxide dielectrics which satisfy requirements of new functionalities. We discussed various nonoxide dielectric materials of organic, self‐assembled mono/multilayers, electrolytes, two‐dimensional (2D) materials, and metal halides. Finally, we conclude with an outlook and challenges on dielectric materials for next‐generation micro‐ and macro‐electronics.